Total and domain-specific self-concepts of Malaysian art school students and their achievements in art subjects - Wong, Xi Ying; Chan, Cheong Jan; Madon, Zainal (University of Malaya, 2021)
In this study, we investigated the profile of self-concept of artistically and musically talented students, urged by the fact that gifted students in general were reported to have low self-concept and suffered from societal-behavioural problems. The study also de-termined the associations of self-concepts and their achievements in art subjects. A to-tal of 232 samples were taken from the Malaysian Art School. Data were collected us-ing Self Description Questionnaire-II (SDQ II), Arts Self Perception Inventory (ASPI) and the results of the students’ Form Three Evaluation (PT3). Artistically talented stu-dents were found to have a moderately high level of self-concept, and their self-con-cept was significantly different between genders and the specific artistic domain they major in. There was also a positive association between total self-concept and academ-ic self-concept with the artistic achievement of the art school students.